Andinia pseudocaulescens - Vieira Uribe, Sebastian (2018)
Andinia pseudocaulescens has a wide distribution and has been found on all three Cordilleras in Colombia as well as in Ecuador. It frequently grows together with other species of Andinia subgen. Brachycladium (Luer) Karremans & S.Vieira-Uribe, but can be rec ognized by the small plants with elliptical leaves that are margin ally ciliate, the burgundy fowers almost as big as the leaves, borne on short inforescences, with ovate, acuminate sepals, and trans versally bilobed, pubescent petals with narrowly oblong lobes.